La memoria y el mito gaullista : usos políticos del pasado en la Francia de la V República (1958-1990) - Lizandra Carvajal García (Amnis)
In French history, more than one symbolic character has been canonized by national memory during the country’s most crucial times. From Jeanne d'Arc to Napoleon, without forgetting Thiers, Clemenceau and Charles de Gaulle, a wide array of images and meanings has developed, from which the archetypal figure of the providential man or the savior has emerged. Under this influence, Charles de Gaulle became the favorite hero of contemporary France, where myth and gaullist memory have developed thanks to a conscious and intentional memory policy. Commemorations, monuments, pilgrimages, museums, books, cinematography, study programs, congresses and souvenirs all make up an arsenal destined to keep well alive the image of the General: the heart of the France Libre, the founder of the Fifth French Republic and the last providential man of the Hexagon-shaped country.